Actor Collaboration in Extreme Poverty Alleviation Policy Formulation in Serang City - Maulana, Delly (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
Poverty is generally defined as the lack of financial resources necessary to meet basic needs, such as food, shelter, and health care. However, poverty is not only limited to financial deprivation, but also includes limited access to essential services such as education, health, and nutrition, which exacerbates the impact of income poverty. Extreme poverty is a condition in which individuals or groups live below the international poverty line, with an income of less than 1.90 per day based on purchasing power parity. Therefore, this research examines the equalization and collaboration of actors and the formulation of poverty alleviation policies in Serang City. The method used is a qualitative method using primary and secondary data and using the Hierarchical Analysis Process (AHP) power analysis technique to obtain a policy strategy. The results showed that the actors that must be involved in poverty alleviation in Serang City are the Central Government, Banten Provincial Government, Serang City Government, Private Sector, Educational Institutions, and Non-Governmental Institutions/Community Organizations. Then the strategy of providing access to education and economic opportunities is a priority strategy to be formulated and implemented to reduce sustainable poverty.